Devulcanized Crumb Rubber as Bitumen Modifier - VASILIEVICI, Gabriel; MIRT, Andreea-Luiza; GHIMIS, Simona; ZAHARIA, Emilian; BOMBOS, Mihaela; BOMBOS, Dorin (Studia Universitatis Babeș-Bolyai Chemia, 2024)
The dispersion of crumb rubber in road bitumen is essential for enhancing the elasticity of asphalt coatings. However, elastomer cross-linking through vulcanization can reduce the colloidal stability of bitumen. This study aims to enhance compatibility by partially devulcanizing crumb rubber using a pulverulent catalyst, specifically phosphomolybdic acid, in a batch reactor at 270°C. The use of a molybdenum-based catalyst is preferred due to its effectiveness in catalyzing the devulcanization process. Additionally, further conditioning of the catalyst through grinding optimizes contact with crumb rubber, enhancing catalyst activity and improving overall compatibility with road bitumen.